Implementasi Peraturan Walikota Ternate Nomor 21 Tahun 2018 Tentang Penggunaan Produk Lokal Khas Daerah Kota Ternate - Hidayat Husin; Sriati Sriati; M. Husni Thamrin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the implementation of Ternate Mayor Regulation Number 21 of 2018 concerning the Use of Local Products Typical of Ternate City, and to determine the factors that influence the implementation of the policy, using a qualitative descriptive method according to the theory of Public Policy Implementation from Donald S. van Metter. and Carl E. van Horn. The results showed that in maximizing the use of local products typical of the Ternate City area as measured by the level of income from product sales at the Tara No Ate Supermarket, 80 percent of the use of local products was dominated by users from outside the City of Ternate, and the remaining 20 percent was utilized by the people of Ternate City. This is because the socialization and motivational activities to the government, namely OPD within the Ternate City Government, Vertical Agencies, BUMN, BUMD, Private, and the community to use local and regional superior products have not been carried out optimally and consistently.